Spot-Centroid Determination Algorithms in Semiactive Laser Photodiodes for Artillery Applications - de Celis, Raúl; Cadarso, Luis (Journal of sensors, 2019)
Precision of guided projectiles depends equally on the accuracy in determining the coordinates of the objective and on the exactness of the measurement devices utilized for position and attitude calculation of the projectile. Development of algorithms for low-cost high-precision terminal guidance systems is a cornerstone in research in this field. Semiactive laser (SAL) kits, and particularly quadrant detector devices, have been developed to improve precision in guided weapons. Photodetection system can be functionally divided into two main parts: sensing and processing. The sensed signal is processed to estimate the spot coordinates, i.e., the laser footprint, which provides some information regarding projectile-target relative position, to obtain the needed information for the navigation and guidance algorithms. The electrical intensities that a real sensor provides under laboratory conditions are compared to a mathematical model based on area intersection calculations to simulate the intensities on real flights. Then, four different processing algorithms, two of them rational, and the other two logarithmic, are tested for different spot sizes, which are nonlinear. Proposing an interpolation algorithm based on the four electrical intensities obtained in a semiactive laser quadrant photodetector, laser footprint center estimation is improved for artillery applications. Finally, an example illustrating a projectile flight is employed to compare real and calculated laser footprints in order to select the best algorithm for artillery applications.